Journey to Dialogue: Sisters of Our Lady of Sion and the Writing of Nostra Aetate - Deutsch, Celia (Studies in Christian-Jewish Relations, 2016)
Scholars have recently examined the work of several groups engaged in the intellectual projects that provided the foundation of Nostra Aetate and, in some cases participated in the writing process. The Sisters of Our Lady of Sion are one of these groups. They are an international women's religious congregation, originally founded with a perspective of conversion that, over the course of a century, developed a commitment to encounter, dialogue and friendship. This article looks at their work in the years preceding the Second Vatican Council, as well as the period of the Council. It then looks at four critical elements that, over the course of several decades allowed the Sisters to make the journey from conversion to dialogue: philosemitism, ressourcement, the Shoah, and the Affaire Finaly. Using administrative documents, it then traces the actual development of thinking from 1946 to 1964. This exploration shows the Sisters' work as being part of a larger context in which women and men, lay people and clergy, scholars and pastoral workers underwent a transformation in the ways in which they understood the relationship of Jews and Christians and made possible a similar transformation in the Church's self-understanding.